2021
DOI: 10.1007/s10903-021-01247-y
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Resilience in Migrants: A Systematic Review of Study and Psychosocial Intervention

Abstract: This systematic review aimed to contribute to a better and more focused understanding of the link between the concept of resilience and psychosocial interventions in the migrant population. The research questions concerned the type of population involved, definition of resilience, methodological choices and which intervention programmes were targeted at migrants. In the 90 articles included, an heterogeneity in defining resilience or not well specified definition resulted. Different migratory experiences were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 113 publications
(201 reference statements)
0
15
0
Order By: Relevance
“…Social connectedness and culture have been shown to greatly influence the outcome of interventions, particularly because these factors impact the manifestation, identification and treatment of psychosocial diseases and mental health symptoms (Ciaramella et al , 2021; Rodriguez and Dobler, 2021). Child-friendly spaces, peer support and mentoring programs may be established to strengthen family and community capacity (Simich and Andermann, 2014; Vindevogel and Verelst, 2020).…”
Section: Recommendations For the Integration Of The Resilience Approa...mentioning
confidence: 99%
“…Social connectedness and culture have been shown to greatly influence the outcome of interventions, particularly because these factors impact the manifestation, identification and treatment of psychosocial diseases and mental health symptoms (Ciaramella et al , 2021; Rodriguez and Dobler, 2021). Child-friendly spaces, peer support and mentoring programs may be established to strengthen family and community capacity (Simich and Andermann, 2014; Vindevogel and Verelst, 2020).…”
Section: Recommendations For the Integration Of The Resilience Approa...mentioning
confidence: 99%
“…The effects of exposure to adverse events are well documented [19,21], and include poor mental health, physical health problems [21,26], and later exposure to violence [77]. A recent meta-analysis estimated a prevalence of 22.71% for post-traumatic stress disorder (PTSD), 13.81% for depression, and 15.77% for anxiety disorders among refugee and asylum-seeking children worldwide in 2003-2018 [11]. In comparison with non-refugee children, both in the countries of origin and resettlement, these numbers stand out as high [11].…”
Section: Exposure To Adversity and Negative Health-related Consequencesmentioning
confidence: 99%
“…; (12) Are the results controlled for confounding? ; (13) Are the results reported in sufficient detail? ; (14) Do the conclusions support the results?.…”
Section: Study Quality and Risk For Biasmentioning
confidence: 99%
“…Current specialized literature, however, emphasizes the need for randomized intervention studies, investigating general mental health conditions such as depression, anxiety, somatization, and functional impairment (Sambucini et al, 2020; Giulia Turrini et al, 2017; Wyk & Schweitzer, 2014). In addition, a systematic review conducted by Ciaramella et al (2021) identified a gap in resilience interventions in the context of migration. They found that out of 90 intervention studies, only five focused on resilience, although considerable evidence shows the importance of resilience for migrants, including refugees.…”
Section: Introductionmentioning
confidence: 99%
“…They found that out of 90 intervention studies, only five focused on resilience, although considerable evidence shows the importance of resilience for migrants, including refugees. They argue that intervention studies usually understand migrants as a homogenous group and ignore within-group differences in life experiences, cultural backgrounds, resources, needs, and vulnerabilities, whereas resilience can mostly be identified and fostered in a context of personal life history and cultural and social background (Ciaramella et al, 2021).…”
Section: Introductionmentioning
confidence: 99%